05 MARJIN PEMASARAN UDANG DI DESA AMPEKALE KECAMATAN BONTOA KABUPATEN MAROS - Jurnal Agribis; Ruslan Ruslan; Arifin Arifin; Azisah Azisah (Universitas Muslim Maros, 2020)
Shrimp is the main product of the export commodities the government for the state foreign exchange so that its been the main focus of its development. The purpose of research is to know the margin marketing by the institutions involved in marketing shrimp and knowledge of marketing channels shrimp happened in in the village of Ampekale, Bontoa District, Maros Regency. This research was conducted in the village of Ampekale, Bontoa District, Maros Regency. There are two data used, namely primary data and secondary data. Data collected from survey results with field observations. Simple random sampling method for the sample of farmers with a total of 12 people. 2 collectors and 1 retailer. 1 person for the exporter company. The analysis used is quantitative analysis. The results of the study are that there are three shrimp marketing channels that occur in Ampekale Village, namely 1.) Producers → Collector traders → Retailers → end consumers; 2.) Producers → collecting traders → companies (exporters); and 3.) Manufacturer → company (exporter). While the shrimp marketing margin in Ampekale Village, Bontoa District, Maros Regency amounting to Rp 3,000 occurred in marketing channel 1, while Rp 2,000 occurred in marketing channels 2 and 3.